SAT0441 Prevalence of Self-Reported Knee Joint Instability and Its Association with Radiographic Features in Severe Knee Osteoarthritis. (15th July 2016) - Leichtenberg, C.; Meesters, J.; Verdegaal, S.; Kaptein, B.; Koster, L.; Kroon, H.; Nelissen, R.; Vliet Vlieland, T.; van der Esch, M.
Abstract : Background: Self-reported knee instability has been reported in 60–80% of all patients suffering from mild to moderate knee osteoarthritis (OA) [1], but the prevalence of self-reported knee joint instability in patients with end-stage OA is unknown. So far, a clear cause for this sense of instability has not been elucidated. Two opposing hypotheses have been described: (i) low knee joint instability is associated with osteophyte formation and (ii) high knee joint instability is associated with joint space narrowing. Objectives: To describe the prevalence of self-reported knee joint instability in patients with end-stage OA and to explore the associations between self-reported knee joint instability and JSN and osteophyte formation. Methods: In this cross-sectional study patients on the waiting list for primary Total Knee Arthroplasty (TKA) in one Dutch hospital were included. The primary outcome measures were preoperative self-reported knee joint instability and radiographic severity (assessed by conventional radiography (CR)). Self-reported knee instability was examined by means of a knee joint instability questionnaire. The item on the presence of knee joint instability was formulated as follows: "the sensation of buckling, shifting or giving way of the knee in the previous 3 months" with the following answering options: 1 never (0 episodes); 2 seldom (1–2 episodes); 3 regular (3–5 episodes); 4 very often (more than 5 episodes). These options were later dichotomized into no episodes of knee joint instability (option 1) or 1 or more episodes of knee instability (option 2–4). Radiographic severity consisted of the presence of osteophyte formation and joint space narrowing (JSN), which were both independently scored for the index knee on a 0–3 scale ranging from 0 no JSN/osteophytes, 1 minute JSN/osteophytes, 2 definite JSN/osteophytes and 3 ankylosis JSN/large osteophytes. These scores were dichotomized into present JSN/osteophyte formation (if JSN/osteophyte score >2) or absent JSN/osteophyte formation (if JSN/osteophyte score <2). Potential confounders included in the logistic regression analyses were patient characteristics (gender, age, body mass index) and joint characteristics (pain, physical function). Results: 227 patients (mean age 68 years; SD 9.0 and 145 females (63%)) were included. Self-reported knee instability was present in 163 patients (72%). The distribution of JSN and osteophyte formation in the total group, the patients with knee joint instability and the patients without knee joint instability is shown in Table 1 . In univariate regression analyses no associations were found between self-reported knee instability and JSN or osteophyte formation (p-values 0.537 and 0.829). Conclusions: In conclusion, the majority (72%) of patients with severe OA reported knee joint instability. Knee joint instability was not associated with either JSN or osteophyte formation. References: Felson D T, Niu J, McClennan C, Sack B, Aliabadi P, Hunter D J, Guermazi A, Englund M. Knee buckling: prevalence, risk factors, and associated limitations in function. Ann Intern Med 2007; 147(8): 534–540. Disclosure of Interest: None declared